Freud and his critics - Robinson, Paul A., 1940- (University of California Press, 1993)
"With admirable clarity, Paul Robinson painstakingly reconstructs and then relentlessly dismantles the arguments of Freud's most tenacious and recent debunkers. The results stunningly vindicate the abiding power of psychoanalysis as a master discourse of our age."--Martin Jay, Professor of History, University of California, Berkeley.